MODERN PEDAGOGICAL MECHANISMS FOR DEVELOPING LABOR EDUCATION IN PRESCHOOL CHILDREN (Journal of Multidisciplinary Sciences and Innovations, 2026)
This article explores modern pedagogical mechanisms for shaping labor education in preschool-aged children. Labor education plays a vital role in developing responsibility, creativity, independence, and social skills in early childhood. The study analyzes contemporary approaches, methods, and technological innovations that contribute to effective labor education in preschool institutions. Various pedagogical tools, interactive learning strategies, and gamified activities are discussed to improve engagement and skill acquisition [1,2]. The article presents practical examples, effectiveness indicators, and a summary table of labor education methods applied in preschool settings.